The formation of the Jewish canon - Lim, Timothy H. (Anchor Yale Bible reference library., 2013)
The discovery of the Dead Sea Scrolls provides unprecedented insight into the nature of the Hebrew Bible or Old Testament before its fixation. Timothy Lim here presents a complete account of the formation of the canon in ancient Judaism from the emergence of the Torah in the Persian period to the final acceptance of the list of twenty-two/twenty-four books in the Rabbinic period.